Pruritus in primary biliary cholangitis: insights from the German PBC registry across secondary and tertiary care : brief report - Herta, Toni; Franke, Annegret; Müller, Tobias; Stein, Kerstin; Bantel, Heike; Günther, Rainer; Denk, Gerald; Reuken, Philipp A.; Schattenberg, Jörn M.; Naumann, Uwe; Böttler, Tobias; Weber, Andreas; et al. (Annals of hepatology, 2026)
Introduction and Objectives - Pruritus is a frequent and burdensome symptom in patients with primary biliary cholangitis (PBC), significantly affecting quality of life. Despite its clinical relevance, data on the prevalence and management, particularly across different levels of healthcare, remain limited. We aimed to assess prevalence, severity, and treatment of pruritus in PBC patients across secondary and tertiary care. - Patients and Methods - Within the German PBC registry, the intensity and management of pruritus were assessed cross-sectionally by treating physicians using a standardized 4-point verbal rating scale (absent, mild, moderate, severe), as well as by analyzing prescribed antipruritic medications. - Results - Pruritus was reported in 23 % (n = 120/515) of patients and classified as mild, moderate, or severe in 59 (49 %), 41 (34 %), and 20 (17 %) cases, respectively. The prevalence of pruritus was 27 % (n = 96/360) for tertiary versus 16 % (n = 24/155) for secondary care (p = 0.006). Moderate or severe pruritus was observed in 13.3 % (n = 48/360) of patients at tertiary centers compared to 8.4 % (n = 13/155) at secondary centers (p = 0.137). Antipruritic therapies were used in only 22.5 % (n = 27/120) patients with pruritus, with bezafibrate being the most frequently prescribed medication (63 %, n = 17/27). Patients with pruritus were more likely to receive antipruritic therapies in tertiary than secondary care: 26 % (n = 25/96) vs. 8 % (n = 2/24) (p = 0.098). - Conclusions - Pruritus in patients with PBC is common and under-treated in the real-world scenario. Assessment and management vary by healthcare level, highlighting the need for standardized care and greater awareness of treatment options across all settings.